Air Induced Formation of Cs3Bi2Br9/Cs3BiBr6 Bulk Heterojunction and Its Dual‐band Photodetection Abilities for Light Communication. (5th August 2022) - Cao, Fa; Li, Ziqing; Liu, Xinya; Shi, Zhifeng; Fang, Xiaosheng
Abstract: Metal‐halide perovskites have long carrier diffusion lengths, low trap densities, and high carrier mobilities, and are therefore of value in the development of photodetectors (PDs). However, the research on dual‐band lead‐free perovskite bulk heterojunction has not been well developed. Here, a novel air induced formation of Cs3 Bi2 Br9 /Cs3 BiBr6 bulk heterojunction, reaching a high‐performance dual‐band photodetecting performance with an ultra‐violet main band (360 nm) peak responsivity of 5.6 mA W −1 and a blue sub‐band (450 nm) peak responsivity of 0.6 mA W −1 at 2 V, is reported. The bulk heterojunction exhibits superior photodetecting performance than that of lateral heterojunction. Furthermore, the PD exhibits a fast response speed (rise time 1.4 µs and decay time 2.0 µs) and good cyclic stability. Theoretical and experimental characterizations suggest Cs3 Bi2 Br9 exhibits a more stable structure in air than that of Cs3 BiBr6 . The dual‐band photodetection abilities of Cs3 Bi2 Br9 /Cs3 BiBr6 bulk‐heterojunction demonstrate great application prospects in light communication. These state‐of‐the‐art findings shed light on the fabrication of novel dual‐band high‐performance PDs based on lead‐free perovskite bulk‐heterojunction. Abstract : In this work, a novel air induced formation of Cs3 Bi2 Br9 /Cs3 BiBr6 bulk heterojunction, is reported and a reasonable growth mechanism is elaborated. Theoretical and experimental characterization suggest that Cs3 Bi2 Br9 exhibits a more stable structure in air. The bulk heterojunction exhibits dual‐band photodetection capabilities, demonstrating great application prospects in light communication. A high‐performance dual‐band photodetection performance with a UV main band (360 nm) peak responsivity of 5.6 mA W −1 and a blue sub‐band (450 nm) peak responsivity of 0.6 mA W −1 at 2 V is achieved.